Impulse performance of synthetic esters based-nanofluid for power transformer. (28th September 2018) - Das, Anu Kumar; Chatterjee, Saibal
Abstract: The lightning impulse breakdown characteristics of a silica nanoparticle based-nanofluid and base oil gaps between electrodes in Type-I and Type-II electrode systems, described in this paper, has been investigated. Based on the analysis of the test results, it has been found that both the mineral oil and synthetic ester oil-MIDEL 7131 based-nanofluid with greater amount of moisture content has higher impulse breakdown strength as compared to its base oil counterparts, with low moisture, in both electrode geometries. Unlike in Type-I electrode system, where there is a linear increase in the enhancement of impulse breakdown strength in nanofluid with nanoparticle concentration level; the enhancement is almost steady in Type-II electrode system, giving an average increase of up to 32% relative to its base oil in the case of synthetic ester while the same is 15% in case of mineral oil, and thus provides interesting possibilities of improvements in the design of insulation structure in ester transformer operating at 400 kV or above. Further, the volt-time characteristics reflect superior performance of nanofluid in withstanding fast events as compared to both base mineral oil and synthetic ester oil. The testing of nanofluid presented, as per the ASTM D3300, for small gap spacing between electrodes considered, will be helpful in assessing the wide scope of the standard in nanofluid research in electric power industry.